Reconceptualizing Corruption as an International Crime: A Review of International Law - Satria Unggul Wicaksana Prakasa (Lampung Journal of International Law)
The discourse surrounding corruption as an international crime is increasingly urgent, as it transcends national borders and contributes to economic crises, conflicts, and various crimes that threaten global security. Scholars such as Christensen (2017), Peters (2018), Davis (2018), and Rothe (2010) have linked corruption to human rights violations, revealing that states often struggle to address it effectively. This research seeks to explore how corruption can be redefined as an international crime and what legal accountability mechanisms exist for perpetrators within international law, while also examining the opportunities for the international community to recognize corruption as an international crime. The findings suggest that corruption crimes impacting security, human rights, and environmental integrity, particularly in contexts where states are unable or unwilling to act, should be classified as international crimes, necessitating a global commitment to amend the United Nations Convention Against Corruption (UNCAC) accordingly. Furthermore, the potential for universal jurisdiction over corruption is explored, whether through amending the 1998 Rome Statute or establishing an ad hoc international tribunal, although significant obstacles remain due to states’ commitments to their sovereignty and criminal jurisdiction.